Global tracking-stabilization control of mobile robots with parametric uncertainty*. Issue 1 (July 2017) - Maghenem, Mohamed; Loria, Antonio; Panteley, Elena
Abstract: We present a simple time-varying controller for tracking problem of mobile robots. We consider the full model of autonomous vehicles, including both the kinematics and the Lagrangian dynamics equations. Our control approach relies on designing a controller at the kinematics level, under any integrable virtual leader velocities, which is robust to any controller, at the torc level, that guarantees that the velocity errors are square integrable. In addition, we assume that the inertia is unknown hence, we use a passivity-based adaptive controller that guarantees the convergence of the velocity tracking errors.